Genomics of the Saccharinae - Paterson, Andrew H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
!
Phylogenetic relationships of Saccharinae and Sorghinae -- The gene pool of Sorghum bicolor and its improvement -- The gene pool of Saccharum species and their improvement -- The gene pool of Miscanthus species and its improvement -- The Sorghum genome sequence: a core resource for Saccharinae genomics -- Transcriptome analysis in the Saccharinae -- Sorghum and Sugarcane Proteomics -- Gene mutagenesis systems and resources for the Saccharinae -- Association Genetics Strategies and Resources -- Sorghum transformation: overview and utility -- Genetic engineering of Saccharum -- Genetic engineering of Miscanthus -- Saccharinae Bioinformatics Resources -- Bridging Classical and Molecular Genetics of Sorghum Plant Stature and Maturity -- Bridging classical and molecular genetics of sorghum disease resistance -- Bridging Conventional and Molecular Genetics of Sorghum Insect Resistance -- Genetic enhancement of sorghum for biomass utilization -- Comparative genomics of grasses: A Saccharinae-centric view -- Comparative genomic analysis of C4 photosynthesis pathway evolution in grasses -- Differentiation of seed, sugar, and biomass-producing genotypes in Saccharinae species -- Perennialism and Weediness in the Saccharinae -- Bringing the benefits of sorghum genomics to Africa -- Synthesis: Fundamental insights into plant biology from the Saccharinae clade.
Keywords: Life sciences; Botany; Plant breeding; Life Sciences; Plant Genetics & Genomics; Plant Sciences; Plant Breeding/Biotechnology.